2013
DOI: 10.1161/strokeaha.113.001116
|View full text |Cite
|
Sign up to set email alerts
|

Explicit Consideration of Baseline Factors to Assess Recombinant Tissue-Type Plasminogen Activator Response With Respect to Race and Sex

Abstract: Background and Purpose-Sex and race reportedly influence outcome after recombinant tissue-type plasminogen activator (rtPA). It is, however, unclear whether baseline imbalances (eg, stroke severity) or lack of response to thrombolysis is responsible. We applied balancing methods to test the hypothesis that race and sex influence outcome after rtPA independent of baseline conditions. Methods-We mapped group outcomes from the National Institute of Neurological Disorders and Stroke (NINDS) dataset based on race a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 35 publications
0
12
1
Order By: Relevance
“…From an epidemiological perspective, the BTS cohort had more females and predominantly Caucasian patients, contrary to the existing knowledge about stroke demographics that AfricanAmerican patients and males bear a higher burden of stroke [25]. The lack of difference in vascular risk factors such as diabetes, hypertension, hyperlipidemia and atrial fibrillation in our study, suggests that other etiologies may play an important role in the causation of strokes in this population.…”
Section: Discussioncontrasting
confidence: 84%
“…From an epidemiological perspective, the BTS cohort had more females and predominantly Caucasian patients, contrary to the existing knowledge about stroke demographics that AfricanAmerican patients and males bear a higher burden of stroke [25]. The lack of difference in vascular risk factors such as diabetes, hypertension, hyperlipidemia and atrial fibrillation in our study, suggests that other etiologies may play an important role in the causation of strokes in this population.…”
Section: Discussioncontrasting
confidence: 84%
“…The identification of such candidate gene expression profiles may also open the opportunity of targeting drugs to such population differences. In addition to African American populations having a higher stroke risk,12 a recent retrospective analysis of rt‐PA studies suggested that African American women show no significant benefit from rt‐PA 13. Analysis of our transcriptome data show a clear transcriptome difference by sex following rt‐PA administration (unpubl.…”
Section: Discussionmentioning
confidence: 77%
“…Traditional risk factors for stroke, such as obesity, hypertension (uncontrolled), and lifestyle only partially account for the higher risk 11. Furthermore, race‐associated differences in response to rt‐PA have been recently described 12, 13. Gene expression studies of vascular disease reveal a difference in the transcriptome of African Americans versus Caucasians 14.…”
Section: Introductionmentioning
confidence: 99%
“…Mandava et al reported that tPA-treated black women had significantly less likelihood of a good outcome (mRS 0-2) compared to white women 3 months following stroke [56]. It was suggested that this differential response to tPA might be due to a higher proportion of blacks presenting with a prothrombotic genotype of plasma inhibitor-1 (PAI-1), an inhibitor of tPA's enzymatic activity [57].…”
Section: Sex Differences In Clinical Strokementioning
confidence: 99%
“…Previous analysis of the NINDS dataset did not show race as a predictor of functional outcome [58] but the study was not powered for subgroup analysis [59]. Therefore, explicit balancing methods were utilized in the study by Mandava et al to evaluate the influence on sex and race on tPA outcome independent on differences in baseline characteristics [56]. Taken together, sex differences in response to stroke treatment may be depend on the ethnicity of stroke patients and further studies that carefully consider baseline characteristics are warranted.…”
Section: Sex Differences In Clinical Strokementioning
confidence: 99%